Turncoat antibodies unmasked in a model of autoimmune demyelination: From biology to therapy - Reza Taghipour-Mirakmahaleh; Françoise Morin; Yu Zhang; Louis Bourhoven; Louis-Charles Béland; Qun Zhou; Julie Jaworski; Anna Park; Juan Manuel Dominguez; Jacques Corbeil; Eoin P. Flanagan; Romain Marignier; et al. (Proceedings of the National Academy of Sciences, 2025)
Autoantibodies contribute to many autoimmune diseases, yet there is no approved therapy to neutralize them selectively. A popular mouse model, experimental autoimmune encephalomyelitis (EAE), could serve to develop such a therapy, provided we can better understand the nature and importance of the autoantibodies involved. Here, we report the finding of autoantibody-secreting extrafollicular plasmablasts in EAE induced with specific myelin oligodendrocyte glycoprotein (MOG) antigens. Single-cell RNA sequencing reveals that these cells produce nonaffinity-matured IgG antibodies. These include pathogenic antibodies competing for shared binding space on MOG’s extracellular domain. Interestingly, the synthetic anti-MOG antibody 8-18C5 can prevent the binding of pathogenic antibodies from either EAE mice or people with MOG antibody disease. Moreover, an 8-18C5 variant carrying the NNAS mutation, which inactivates its effector functions, can reduce EAE severity and promote functional recovery. In brief, this study provides not only a comprehensive characterization of the humoral response in EAE models but also a proof of concept for a therapy to antagonize pathogenic anti-MOG antibodies.